Inhibiting DNA Methylation Improves Survival in Severe Sepsis by Regulating NF-κB Pathway - Cao, Luxi; Zhu, Tingting; Lang, Xiabing; Jia, Sha; Yang, Yi; Zhu, Chaohong; Wang, Yucheng; Feng, Shi; Wang, Cuili; Zhang, Ping; Chen, Jianghua; Jiang, Hong (Frontiers in Immunology, 2020)
Organ dysfunction caused by sepsis is life-threatening and results in high mortality. Therapeutic options for sepsis are limited. Pathogenic factors are considered as components of environmental pressure that modify DNA methylation patterns thereby enhancing disease progression. Here, we found that sepsis patients exhibited higher levels of genomic DNA methylation patterns and hypermethylated genes associated with the NF-kB signaling pathway. Therefore, we hypothesized that a DNA methyl transferase inhibitor, Decitabine, may mitigate inflammation and improve survival by inhibiting the NF-κB signaling pathway. To test the hypothesis, mice challenged with caecal ligation and puncture (CLP) were subcutaneously injected with Decitabine solution (0.5, 1 and 1.5mg/kg) 2 h following operation. Our results indicated that Decitabine reduces DNA methyltransferases (DNMTs), attenuates NF-κB activation, downregulates inflammatory cytokine levels, and inhibits the progression of sepsis. Thus, DNA methylation may be indispensable for sepsis and serve as a predicting factor. The use of Decitabine could represent a novel strategy in the treatment of sepsis.